A systematic bibliometric analysis on the clinical practice of CGM in diabetes mellitus from 2012 to 2022 - Kong, Laixi; Deng, Bei; Guo, Maoting; Chen, Mengjie; Wang, Xiaoxia; Zhang, Mingjiao; Tang, Hongxia; Wang, Qin; Yang, Liwei; Xiong, Zhenzhen (Frontiers in Endocrinology, 2023)
Background: Continuous glucose monitoring (CGM) has revolutionized diabetes management, but a comprehensive analysis of its clinical implementation is lacking. This study aims to explore CGM in diabetes practice over the past decade using bibliometric analysis. It will identify trends, research focal points, and provide a framework for future investigations.The Web of Science Core Collection (WOSCC) was utilized to acquire literature pertaining to the employment of continuous glucose monitoring (CGM) in diabetes that was published between the years 2012 and 2022, and to conduct a comprehensive analysis of the associated citation data. To achieve bibliometric visualization and analysis of the collated data, the bibliography package in the Rstudio(v.4.2.2), Citespace 6.2.R4, and VOS viewer were employed.Results: A total of 3024 eligible publications were extracted from 91 countries, with the United States being the leading country in terms of the number of issued articles. Furthermore, the annual publication rate has shown a gradual increase during the past decade. Among the various journals in this field, DIABETES TECHNOLOGY & THERAPEUTICS was identified as the most highly cited one.Keyword clustering analysis of the extracted publications indicates that the research hotspots in the past decade have primarily focused on "continuous glucose monitoring", "glycemic variability", "type 1 diabetes", "hypoglycemia", and "glycemic control". Moreover, the analysis of keyword emergence reveals that "Time In Range" and "Young Adult" represent the current research frontiers for the years 2012-2022. This is a provisional file, not the final typeset articleThe concept of Time in Range (TIR) has garnered considerable attention as a significant area of inquiry and an emerging research trend in the clinical practice of Continuous Glucose Monitoring (CGM) for Diabetes Mellitus. Moreover, recent investigations have demonstrated a growing focus on young adults with type 1 diabetes as the research population of interest. In the foreseeable future, research endeavors will persist in the pursuit of improving glycemic management among young adults through the utilization of continuous glucose monitoring (CGM) technology, while also delving into the examination of the Time in Range metric via supplementary clinical investigations.